A STUDY ON DEMOGRAPHIC VARIABLES AND RESPONDENTS PERCEPTION TOWARDS ENVIRONMENTAL ISSUES CAUSED BY OUTDOOR ADVERTISING CHANNELS - Sachin Subhashchand Surana, Dr. Hansraj Madhukar Patil (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Nowadays advertising had become an important source of sales promotion. It drives the existing and potential customers towards offering of the business organisations. Various indoor and outdoor advertising channels are frequently used to stimulate demands for products and services. Outdoor advertising refers to any advertising instruments located outside home. Outdoor advertising channels can be observed all around city areas to capturing the attention of the onlookers. It prominently includes hoardings, posters, banners, flex, and wall paintings. While outdoor advertising channels effectively raise awareness of products and services, they can also pose environmental challenges and create disturbances in surrounding areas. The present research is carried out to identify environmental issues caused by outdoor advertising channels Study revealed that outdoor advertising channels creates various detrimental effect on environment. Study concluded that there is no significant difference between demographic variables and respondents opinion that outdoor advertising channels causes various environmental problems.